Seasonal lipid dynamics of the copepods Pseudocalanus minutus (Calanoida) and Oithona similis (Cyclopoida) in the Arctic Kongsfjorden (Svalbard) - Lischka, Silke; Hagen, Wilhelm (Marine Biology, 2007)
Seasonal lipid dynamics of various developmental stages were investigated in Pseudocalanus minutus and Oithona similis. For P. minutus, the dominance of 16:1(n−7), 16:4(n−3) and 20:5(n−3) fatty acids indicated a diatom-based nutrition in spring, whereas 22:6(n−3), 16:0, 18:2(n−6) and 18:1(n−9) pointed to a flagellate-based diet during the rest of the year as well as omnivorous/carnivorous low-level feeding during winter. The shorter-chain fatty alcohols 14:0 and 16:0 prevailed, also reflecting biosynthetic processes typical of omnivores or carnivores. Altogether, the lipid signatures characterized P. minutus as an opportunistic feeder. In contrast, O. similis had consistently high amounts of the 18:1(n−9) fatty acid in all stages and during all seasons pointing to a generally omnivorous/carnivorous/detritivorous diet. Furthermore, the fatty alcohol 20:1(n−9) reached high percentages especially in adult females and males, and feeding on Calanus faecal pellets is suggested. Fatty alcohols, as wax ester moieties, revealed significant seasonal variations in O. similis and a seasonal trend towards wax ester accumulation in autumn in P. minutus. P. minutus utilized its lipid deposits for development in the copepodite stages III and IV and for gonad maturation in CV and females during the dark season. However, CVs and females depended on the spring phytoplankton bloom for final maturation processes and reproduction. O. similis fueled gonad maturation and egg production for reproduction in June by wax esters, whereas reproduction in August/September co-occurred with the accumulation of new depot lipids. Both species revealed significantly higher wax ester levels in deeper (>50 m) as compared to surface (0–50 m) dwelling individuals related to a descent prior to overwintering.